Practising critical reflection a resource handbook - Fook, Jan; Gardner, Fiona (Open University Press, 2007)
Focuses on a description and analysis of the theoretical input as well as the approach involved in critical reflection. his work also demonstrates some skills, strategies and tools which might be used to practise it. It is suitable for students across social work, and health sciences as well as health care and social welfare professionals.